Tuning the exchange bias effect via thermal treatment temperature in bulk Ni50Mn42In3Sb5 Heusler alloys. (13th September 2021) - Cao, Kaiyan; Tian, Fanghua; Huang, Shuo; Zhang, Yin; Zhao, Qizhong; Yao, Kangkang; Dai, Zhiyong; Li, Jianing; Yu, Zhonghai; Zhou, Chao; Ke, Xiaoqin; Song, Xiaoping; et al.
Abstract: An interesting evolution of spin glass behaviors and the corresponding exchange bias effects were observed by quenching Ni50 Mn42 In3 Sb5 Heusler alloys at different temperatures. When the alloy is quenched at 1173 K, it will freeze from antiferromagnetic to spin glass at low temperature under an external magnetic field, creating a giant exchange bias field up to 9063 Oe through the pinning effect. In another case, the superparamagnetic in alloys quenched at 473 K will transform to superspin glass after zero-field cooling at low temperatures instead. As a result, a spontaneous exchange bias effect up to 581 Oe can be achieved.